The efficacy of Netrod Six-electrode Radiofrequency Renal Denervation system: mathematical modeling, phantom experiments and animal studies - Xiaohua Song; Jiulin Guo; Hongguang Cao; Qun Nan (PLoS ONE, 2025)
The principle of NetrodTM Renal Denervation RF Generator is based on the heating of radiofrequency electrodes to achieve the therapeutic temperature for peripheral nerve ablation with minimal impact on intra-arterial blood flow. The extravascular heat distribution and continuous ablation were evaluated using COMSOL Multiphysics with an idealized 3D model and validated in an ex vivo experiment. The safety of ablation was verified by H&E staining of a hypertensive dog model in the treatment group of animal experiments, and changes in blood pressure before and after the procedure(assessed at 7, 30, and 60 days in animal experiments) were used to characterize the efficacy. The simulation results showed that the maximum injury depth range of the NetrodTM Six-electrode is 5.08mm and the depth of the ablation zone obtained in the Phantom experiment was 3–6mm. Circumferential coverage was up to 91.99% and the ablation zone was continuous. In animal experiments, eight animals in the treatment group had significantly lower blood pressure (88.9%). Nerve cells in nerve bundles showed vacuolar changes and thickening of peripheral sheaths after peripheral nerve ablation of renal arteries.The NetrodTM Six-electrode presented here has potential to effectively and safely ablate renal nerves. The demonstrated efficacy and safety in animal models provide a foundation for clinical trials in humans.